Analysis of Amino Acid Patterns With Nutrition Regimens in Preterm Infants With Extrauterine Growth Retardation - Wang, Li; Liu, Danyang; Shen, Haiqing; Wang, Ying; Han, Lianshu; He, Zhenjuan (Frontiers in Pediatrics, 2020)
Abstract Background: Amino acid (AA) metabolic patterns have emerged as an analytical technique to characterize biomarkers compromising normal growth and elucidate underlying nutritional exposure. This study aimed to identify AA metabolites most likely associated with poor growth and examine the association between AA metabolites and nutrition regimens in preterm infants during transition from parenteral nutrition (PN) to enteral nutrition (EN), using gas chromatography-mass spectrometry (GC-MS). Methods: This observational cohort study was conducted in infants born at <32 weeks’ gestation with birth weight of <1500 g. The outcome of extrauterine growth retardation (EUGR) based on whether the weight was <10th percentile for post-menstrual age, was evaluated when full EN reached. Samples were collected at four sampling points according to nutritional status. AA profiles in dried sampling point spots (DBS) were quantified using GC-MS; and were compared simultaneously. The correlation of AA concentration with growth and nutritional parameters was examined using multivariate analysis. Results: We identified 40 eligible infants: 20 in the EUGR group and 20 in the non-EUGR group. AA deficiency progressively emerged during the transition. Lower concentrations of four AAs, including citrulline (Cit), were associated with increased risk of EUGR when adjusted for gestational age, birth weight z-score, age when trophic EN was started, as well as average energy and protein intakes in synchronous nutritional period. Moreover a lower Cit concentration was positively correlated with the compromised protein and energy deficits in EN during early transition. Conclusion: A low Cit concentration during transition from PN to full EN should be noticed by the clinician to more closely examine nutrition practices to prevent EUGR.